(3HdhZ GdZGjI aj TQM GdcaGjIs - (3GdMSjfj GdMdj, eSde Hf MehO, (B1401 (3g`s ((3GdeDdas)
(3ChdgG (B:s
(3GdMeO ddg (B... (3GdcdGe aj GdChGeQ ; bhdg (B( (3eGOI GdCeQ (B) (3eGOI GdTjA eG Hg bhI hLhOg , aeGOI GdGeQ YHGQI Yf MQhag GdeJQcH efgG daXg (B...s
(3BNQgG (B:s
..(3HeYfi JhLg GdGdJaGJ EdjgG aEfg CeQ hLhOj , bhdg (B( (3cSGFQ GdehVhYGJ GdeJbOeI HCeQ YOej (B) (3Cj ajLQj GdCUd dEKHGJgG HEKHGJ bhGegG GdYOej (B. (3GfJgis
(3eHjVI GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3CUhd Gdabgs